ANALISIS PENGELOLAAN SUMBER DAYA MANUSIA PADA LEMBAGA PENDIDIKAN MENYONGSONG IMPLEMENTASI KURIKULUM MERDEKA - Muchlip M, Cipnal (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Management of human resources is absolutely necessary in an institution ororganization. Unfortunately, management practices in educationalinstitutions have not been carried out properly and systematically. This studyaims to analyze the practice of managing human resources in schools, especiallyin relation to the implementation of the independent curriculum. The researchmethod used in this research is descriptive qualitative. Data obtained throughinterviews and observation. Interviews were conducted with teachers, principalsand vice curricula. The results of the study show that (1) most schools do nothave a special department in charge of managing human resources. (2) Schoolsenthusiastically welcome the implementation of the independent curriculum,although they feel that there are still many things they don't know and needto know (3) The independent curriculum requires teachers to haveindependence, self-integrity. An independent curriculum decmands that everyteacher has learning and teaching independence, for this reason it is necessaryto manage teaching and educational staff so that they are in harmony with thechallenges of Kurikulum Merdeka.